Peer Feedback, Problems, Teacher Roles and the Learning Process - Alinsangan, Paula (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Through peer feedback or peer reviews, students work in small groups to read each others compositions and give comments and suggestions for improvement. Aside from the benefit of receiving help to improve their compositions, students benefit from peer feedback in many other ways: they develop a sense of audience, they hone their critical ability, they develop a sense of responsibility, cooperation and trust, etc. However, doing peer feedback may not be that easy. In this article, the author presents the problems that she has encountered in using peer feedback with freshman college students. These problems involve socio- affective, communicative and cognitive problems. She also presents some practical decisions she has made in dealing with these problems. In her experiences of trying to find out ways and means to make peer feedback work, she has understood better the multiple roles of the teacher and the learning process. For her, using peer feedback as a teaching technique has been a learning experience.